Journal of biological systems. (Singapore ; New York : World Scientific, 1993)
Access available from 2001-
Keywords: Biological systems -- Periodicals; Biological systems -- Mathematical models -- Periodicals; Biomathematics -- Periodicals; System analysis -- Periodicals; Biology -- Periodicals; Biometry -- Periodicals; Medicine -- Periodicals; Models, Biological -- Periodicals; Models, Theoretical -- Periodicals; Systems Theory -- Periodicals; Biologisches System; Zeitschrift